PM2b, a CC-NBS-LRR protein, interacts with TaWRKY76-D to regulate powdery mildew resistance in common wheat - Jin, Yuli; Liu, Hong; Gu, Tiantian; Xing, Lixian; Han, Guohao; Ma, Pengtao; Li, Xiuquan; Zhou, Yilin; Fan, Jieru; Li, Lihui; An, Diaoguo (Frontiers in Plant Science, 2022)
Powdery mildew caused by Blumeria graminis f. sp. tritici (Bgt) is a destructive disease of wheat throughout the world. Host resistance is considered the most sustainable way to control this disease. Powdery mildew resistance gene Pm2b was mapped to the same genetic interval with Pm2a and PmCH1357 cloned previously, but showed different resistance spectra from them, indicating that they might be caused by different resistance genes or alleles. In this study, Pm2b was delimited to a 1.64 Mb physical interval using a large segregating population containing 4,354 F2:3 families of resistant parent KM2939 and susceptible cultivar Shimai 15. In this interval, TraesCS5D03G0111700 encoding the coiled-coil nucleotide-binding site leucine-rich repeat protein (CC-NBS-LRR) was determined as the candidate gene of Pm2b. Silencing by barley stripe mosaic virus-induced gene silencing (BSMV-VIGS) technology and two independent mutants analysis in KM2939 confirmed the candidate gene TraesCS5D03G0111700 was Pm2b. The sequence of Pm2b was consistent with Pm2a/PmCH1357. Subcellular localization showed Pm2b was located on the cell nucleus and plasma membrane. Pm2b had the highest expression level in leaves and was rapidly up-regulated after inoculating with Bgt isolate E09. The yeast two-hybrid (Y2H) and luciferase complementation imaging assays (LCI) showed that PM2b could self-associate through the NB domain. Notably, we identified PM2b interacting with the transcription factor TaWRKY76-D, which depended on the NB domain of PM2b and WRKY domain of TaWRKY76-D. TaWRKY76-D negatively regulated the resistance to powdery mildew in wheat. The specific KASP marker K529 could take the advantage of high-throughput and high-efficiency for detecting Pm2b and be useful in molecular marker assisted-selection breeding. In conclusion, cloning and disease resistance mechanism analysis of Pm2b provided an example to emphasize a need of the molecular isolation of resistance genes, which has implications in marker assisted wheat breeding.